Interpretation of the Tensile Strength of Ice Under Triaxial Stresses - Nevel,Donald E.; Haynes,F. Donald (1976)
Griffith, and later Babel, have previously developed a tensile fracture criterion for a two-dimensional state of stress. This theory is extended to the compression-compression region. From this theory the angle of fracture is developed. The theory is extended conceptually to three dimensions. Triaxial test data by Haynes for snow-ice are shown in this three-dimensional fracture theory. The test data are slightly less than those predicted when the void in the snow-ice is spherical. (Author)